A note on the rational homological dimension of lattices in positive characteristic. (10th January 2023) - Hughes, Sam
Abstract: We show via ^2 -homology that the rational homological dimension of a lattice in a product of simple simply connected Chevalley groups over global function fields is equal to the rational cohomological dimension and to the dimension of the associated Bruhat–Tits building.